1996
DOI: 10.1063/1.868827
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale properties of nonlinear interactions and subgrid-scale energy transfer in isotropic turbulence

Abstract: Using results of direct numerical simulations of isotropic turbulence the subgrid-scale energy transfer in the physical space is calculated exactly employing a spectral decomposition of the velocity field into large (resolved) and small (unresolved) scales. Comparisons with large-scale quantities reveal large qualitative correlations between regions of subgrid transfer and the boundaries of regions of large vorticity production. This suggests a novel analysis of the nonlinear term, where it is decomposed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 35 publications
1
30
1
Order By: Relevance
“…There are many differences between the DNS analysis, the parameterization tests using decaying, isotropic turbulence, and the channel flow LES. These are that a wavenumber cut-off filter was used in the DNS analysis 17 instead of a Helmholtz filter as we now believe is correct, the Leray terms have never been tested in DNS analysis, and a Smagorinsky eddy viscosity was used for the decaying, isotropic LES tests instead of the k − l eddy viscosity. New DNS analysis is planned to determine the effect of these differences and the decaying, isotropic LES tests will be repeated with a k − l eddy viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are many differences between the DNS analysis, the parameterization tests using decaying, isotropic turbulence, and the channel flow LES. These are that a wavenumber cut-off filter was used in the DNS analysis 17 instead of a Helmholtz filter as we now believe is correct, the Leray terms have never been tested in DNS analysis, and a Smagorinsky eddy viscosity was used for the decaying, isotropic LES tests instead of the k − l eddy viscosity. New DNS analysis is planned to determine the effect of these differences and the decaying, isotropic LES tests will be repeated with a k − l eddy viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of DNS, 17 it was found that in addition to backscatter generated by subgrid terms, there was a second term that was dissipative and was similar to the prediction of an eddy viscosity model. It has been claimed that the regularization models, without eddy viscosities, are an alternative method of LES.…”
mentioning
confidence: 99%
See 3 more Smart Citations